Simplified approach to DFT computation for nonprogrammable scientific calculators - Yasin, Mohd Yusuf (BIBECHANA, 2014)
Fourier analysis is an important tool used as it is or it’s different variants in many fields of sciences and engineering. It’s importance is due to it’s simplicity with which it expands a given function in terms of circular or complex exponents. Further it is quite versatile to handle many functions of practical interest, specifically, the functions with several mathematical disabilities that are hard to be handled with tools like Taylor series. Discrete Fourier Transform (DFT) is a form of Fourier analysis where the discrete function and it’s transform are both of finite length. This processing requires lot many computations. Here in this work a simplified and non programmable calculator based scheme is presented with which one can easily determine the DFT of the given function by feeding in the DFT equation once and a few presses of the calculator keys. DOI: http://dx.doi.org/10.3126/bibechana.v12i0.11681 BIBECHANA 12 (2015) 13-19